BDNF variant Val66Met interacts with estrous cycle in the control of hippocampal function - Spencer, Joanna L. (National Academy of Sciences, 2010)
Natural fluctuations in circulating estradiol are associated with behavioral changes, including severe disturbances in mood and cognition in some women. Common genetic variation in some of the molecular mediators of estradiol effects on these behaviors, in brain regions such as the hippocampus, may explain individual variation in estradiol effects on behavior. We tested whether the common human variant BDNF Val66Met interacts with estradiol in the control of hippocampal function in cycling female mice homozygous for the wild-type Val or BDNF Met variant. BDNF Met increased anxiety behavior, impaired memory, and increased expression of BDNF and its receptor TrkB in the hippocampal formation. BDNF Met also dramatically altered the fluctuation of spatial memory, hippocampal Akt phosphorylation, and PSD-95 protein expression across the estrous cycle. The variant BDNF Val66Met should therefore be considered as a strong candidate for mediating genetic differences in ovarian steroid-related behavioral changes and disorders.